Entrepreneurial culture and entrepreneurial intention: A comparative study between Peruvian and Paraguayan university students through the theory of planned behavior - Vera, Kerwin José Chávez; Velita, Joel Joab Alderete; Alcala, Ascencion Tomas; Mónaca, Salvador; Ferrer, Raul Marcelo (International Journal of Innovative Research and Scientific Studies, 2025)
The study focuses on the analysis of entrepreneurial intention among university students in Peru and Paraguay, using the Theory of Planned Behavior (TPB) as a theoretical framework. The relationship between entrepreneurial culture, institutional support, perception of barriers, and the influence of innovation and creativity on entrepreneurial intention is investigated. Employing a quantitative approach, data were collected from 395 students using a 55-item structured questionnaire, validated by experts and with a Cronbach's Alpha reliability of 0.89. The results show that entrepreneurial culture and institutional support have a significant impact on entrepreneurial intention, while the perception of barriers shows no significant relationship. In addition, innovation and creativity are identified as key drivers of entrepreneurship. This study contributes to the existing literature on entrepreneurship and offers recommendations for educational institutions and economic policies that seek to foster an entrepreneurial climate in the region, highlighting the importance of self-efficacy and a favorable environment for the development of entrepreneurial initiatives.